1994
DOI: 10.1021/bi00189a001
|View full text |Cite
|
Sign up to set email alerts
|

Determination by Raman Spectroscopy of the pKa of N5 of Dihydrofolate Bound to Dihydrofolate Reductase: Mechanistic Implications

Abstract: Dihydrofolate reductase (DHFR) catalyzes the reduction of dihydrofolate (H2folate) to tetrahydrofolate by NADPH, and this requires that the pteridine ring be protonated at N5. A long-standing puzzle has been how, at physiological pH, the enzyme can protonate N5 in view of its solution pKa of 2.6 and the fact that the only proton-donating group in the pterdine binding site, Asp-27, hydrogen bonds not to N5 but to the 2-amino group and N3 of the pterin ring. We have determined the pKa of N5 of dihydrofolate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
140
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 29 publications
12
140
0
Order By: Relevance
“…For Type I DHFR, it is generally thought that the protonation step precedes hydride transfer, thus creating a cationic intermediate which will more readily accept the hydride ion (45)(46)(47). Consistent with this view, vibrational spectroscopic studies have demonstrated that the N5 pK a of DHF is increased from 2.6 to 6.5 upon complex formation with E. coli DHFR (12)(13)(14)(15). In the type I enzyme, this protonation step is thought to involve an active site aspartyl (bacterial) or glutamyl (mammalian) residue.…”
Section: Catalytic Mechanismmentioning
confidence: 92%
See 2 more Smart Citations
“…For Type I DHFR, it is generally thought that the protonation step precedes hydride transfer, thus creating a cationic intermediate which will more readily accept the hydride ion (45)(46)(47). Consistent with this view, vibrational spectroscopic studies have demonstrated that the N5 pK a of DHF is increased from 2.6 to 6.5 upon complex formation with E. coli DHFR (12)(13)(14)(15). In the type I enzyme, this protonation step is thought to involve an active site aspartyl (bacterial) or glutamyl (mammalian) residue.…”
Section: Catalytic Mechanismmentioning
confidence: 92%
“…These studies have shown that the pK a of N5 in the complex is < 4 (15), compared to the free pK a of 2.60 (35,52). Both these values compare with an N5 pK a value of 6.5 for DHF bound to the Type I enzyme from E. coli (12,13). These results demonstrate that elevation of the N5 pK a represents an important strategy for optimization of the catalytic rate constant for the chromosomal enzyme, while this perturbation apparently is not achieved for the Type II enzyme.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…This assumes that the substrate carboxylate group and active-site side-chain functional groups are ionized, as found spectroscopically for functional groups in other enzymes (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The pyruvoyl dependent histidine decarboxylase does place its substrate carboxylate in a nonpolar environment (19), and nonpolar binding sites were successfully employed in the generation of PLP-dependent catalytic antibodies (20).…”
mentioning
confidence: 99%
“…Moreover, this conclusion agreed well with pH-dependent kinetic and mutagenesis studies of the E. coli enzyme (4, 13, 14). A protein-induced "preprotonation" of N5 goes a long way toward understanding the catalytic mechanism because N5 must protonate along the pathway and also ab initio calculations suggest that protonation will facilitate hydride transfer (10,15,16). On the other hand, difference Raman studies of dihydroneopterin aldolase, another enzyme in the folate synthesis pathway whose structural and chemical similarities to E. coli DHFR prompted the suggestion of a reaction mechanism similar to that of chromosomal DHFRs (17), found that N5 is unprotonated above pH 6 (18).…”
mentioning
confidence: 99%